Incidental finding of hepatic pseudolesion from aberrant right gastric vein in a breast cancer patient - Sawafta, Ahmed (2025)
Aberrant right gastric veins (ARGV) represent rare anatomical variations that can result in hepatic pseudolesions, mimicking malignancies due to their atypical drainage directly into the liver parenchyma. This case highlights a 44-year-old woman initially presenting with a breast mass incidentally found to have an ARGV-related pseudolesion in hepatic segment IVa. ARGV is clinically significant as it can alter hepatic blood flow dynamics, leading to hyperdense or hypodense regions on imaging. Recognizing these pseudolesions is essential to avoid misdiagnosis, unnecessary procedures, and to distinguish them from true hepatic lesions. This case emphasizes the importance of advanced imaging modalities in diagnosing such anomalies, ensuring accurate patient management.